Citrate and the regulation of adipose-tissue phosphofructokinase - Denton, R. M. (1966)
1. Methods are described for the extraction, partial purification and assay of phosphofructokinase in rat epididymal adipose tissue. 2. The enzyme was inhibited by ATP at concentrations above 20μm and by citrate; the enzyme was activated by ADP, AMP, 3′,5′-(cyclic)-AMP, phosphate and sulphate. 3. The enzyme lost activity on incubation at 25° or during chromatography on DEAE-cellulose unless fluoride at a concentration of 4mm was present. 4. The significance of these results in relation to the role of glycolysis and citrate in lipogenesis is discussed.